2010
DOI: 10.1007/s12017-010-8112-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cytokines as Mediators and Regulators of Microglial Activity in Inflammatory Demyelination of the CNS

Abstract: As the resident innate immune cells of the central nervous system (CNS), microglia fulfil a critical role in maintaining tissue homeostasis and in directing and eliciting molecular responses to CNS damage. The human disease Multiple Sclerosis and animal models of inflammatory demyelination are characterized by a complex interplay between degenerative and regenerative processes, many of which are regulated and mediated by microglia. Cellular communication between microglia and other neural and immune cells is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 449 publications
(457 reference statements)
0
57
0
1
Order By: Relevance
“…A number of studies have shown that the expression of iNOS and COX-2, key enzymes for NO, is upregulated in activated glial cells. Pro-inflammatory cytokines such as TNF-a and IL1b are also initiators of the inflammatory response and mediators in the pathogenesis of neurodegenerative disorders [23,24]. Previous evidence has demonstrated the damaging and inflammatory effects of these cytokines in neuropathology [25].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that the expression of iNOS and COX-2, key enzymes for NO, is upregulated in activated glial cells. Pro-inflammatory cytokines such as TNF-a and IL1b are also initiators of the inflammatory response and mediators in the pathogenesis of neurodegenerative disorders [23,24]. Previous evidence has demonstrated the damaging and inflammatory effects of these cytokines in neuropathology [25].…”
Section: Discussionmentioning
confidence: 99%
“…), there has not been an association found between pain and the site of demyelination 19 though it has been associated with depression, spinal cord involvement at the onset and the presence of spinal cord lesions 3 . The damage to the pain pathways has been theorized to possibly involve glia and cytokines 20 , which has been linked to the possible mechanism of central pain 21 . However, no significant pain relief has been found with any of the disease modifying medications that target the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The activation, proliferation, recruitment, and conversion of microglia to a phagocytic amoeboid phenotype is an important cellular response that contributes to clearance of myelin debris in various models of CNS demyelination (Merson et al, 2010). In contrast, DT-challenged MBP-DTR mice exhibited only a modest increase in microglial cell density that retained a ramified morphology with evidence of process thickening reminiscent of "prephagocytic" lesions in early MS cases (Barnett and Prineas, 2004), and "predemyelinating" lesions described by Marik et al (2007).…”
Section: Immune Activity and Myelinationmentioning
confidence: 99%